How to: Design to include women - Larson, A.M.; Sarmiento Barletti, J.P. (CIFOR-ICRAF, 2023)
Multi-stakeholder platforms (MSPs) aim to field and include a broad range of perspectives in decision-making processes on land and resources. But women and particularly Indigenous and local community women often lose out on meaningful representation in these platforms.